Association Between Oxidative Stress and Altered Cholesterol Metabolism in Alzheimer’s Disease Patients - Zarrouk, Amira; Hammouda, Souha; Ghzaiel, Imen; Hammami, Sonia; Khamlaoui, Wided; Ahmed, Samia H.; Lizard, Gérard; Hammami, Mohamed (Current Alzheimer Research, 2020)
Background: Oxidative stress is the main feature of several diseases including Alzheimer’s disease (AD). The involvement of oxysterols derivates has been recently reported. Objective: The aim of this study was to evaluate the implication of oxidative stress in cholesterol impairment in AD patients. Methods: A case-control study was conducted on 56 AD patients and 97 controls. Levels of oxidative biomarkers, including lipid peroxidation products and antioxidant enzyme activities were measured with spectrophotometric methods on red blood cells (RBCs) and plasma. Cholesterol precursors and oxysterols (7-Ketocholeterol (7KC), 7α-hydroxycholesterol (7α-OHC), 7β-hydroxycholesterol (7β-OHC), 24Shydroxycholesterol (24S-OH), 25-hyroxycholesterol (25-OHC), and 27-hydroxycholesterol (27-OHC), in plasma were quantified by gas chromatography coupled with mass spectrometry. Results: In RBCs and plasma of AD patients, a significant decrease of glutathione peroxidase (GPx) activity was detected associated with raised levels of malondialdehyde (MDA). A decreased level of lanosterol and an accumulation of 7β-OHC, 24S-OHC, 27-OHC, and 25-OHC that were higher in plasma of AD patients, compared to controls, were also observed in AD patients. Mini-Mental State Examination (MMSE) score was correlated with MDA and conjugated dienes (CD) levels in plasma. Besides, the MDA level in RBCs was correlated with 7β-OHC. Binary logistic regression revealed an association between GPx activity and AD (OR=0.895, 95%CI: 0.848-0.945. P<0.001). Conclusion: Our data consolidate the relationship between the rupture of redox homeostasis and lipid and cholesterol oxidation in AD.
Keywords: Alzheimer' s disease